Cooperative and Noncooperative R&D in Duopoly With Spillovers - d'Aspremont-Lynden, Claude; Jacquemin, Alexis (American Economic Review, 1988)
Contrary to the usual assumption made in most oligopoly models, relations among firms are seldom of a wholly cooperative or noncooperative type: in many situations, they compete in some fields, while they cooperate in others. An important example is the case of cooperative research efforts bringing fierce competitors together. Two types of agreement are observed. First R&D cooperation can take place at the so-called “precompetitive stage”: companies share basic information and efforts in the R&D stage but remain rivals in the market-place.1 A second type of agreement involves an extended collusion between partners, creating common policies at the product level. The usual justifications of this extension are the difficulties of protecting intellectual property. The idea is then to allow partners who have achieved inventions together, to also control together the processes and products which embody the results of their collaboration, in order to recuperate jointly their R&D investments.2 What could be expected from these types of agreement is a reduction in R&D expenditures, because of less wasteful duplication, and a reduction of total production, because of more ∗Reprinted from The American Economic Review, 78(5), 1133-1137, 1988. †Center for Operations Research & Econometrics, 1348 Louvain-la-Neuve, Belgium. We are grateful to Jean